Paratextos Ficcionais Em Watchmen - Brito, Karoline Caetano [UNIFESP] (2018)
This Research Focuses On The Multimodal Texts Presented At The End Of The First 11 Chapters Of Watchmen, A North American Comic Book Scripted By Alan Moore And Designed By Dave Gibbons Published In The United States As A Maxisserie In 12 Editions Between The Years Of 1986 And 1987. Our Main Objective Is To Understand The Role That These Texts, Which We Consider Fictional Paratexts, Exert On The Work. For The Analysis, Will Be Adopted The Portuguese Language Edition Published By Panini Books In 2011. Our Hypothesis Is That There Are Non-Fictional Paratexts - Which Are Related To The Published Work, Such As The Title, Preface, Cover, And So On - And Fictional - That Were Produced In The Fictitious Context And Do Not Exist In Any Other Way - Having Our Corpus Framed In The Second Case. What Is Proposed Here Is To Conduct A Dialogue Between Literature, Linguistics And Comics, Using The Concepts Of Paratexts Presented By Genette (1989; 2009); The Contextualisation Factors Of Marcuschi (2012); Hypertext Reading, Ac